Analisis Produktivitas Melalui Metode Terintegrasi OEE, FMEA, dan TPM pada Mesin Hydraulic Dished End Press (Studi Kasus: PT. Meco Inoxprima) - Nadya Shavira Julia Azzahra; Wiwin Widiasih (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Machine productivity is a critical factor in the success of manufacturing production systems. This study aims to analyze the effectiveness of the Hydraulic Dished End Press at PT Meco Inoxprima and identify the primary causes of the machine’s performance decline using an integrated approach combining OEE, FMEA, and TPM. Based on operational data from September 2025 to February 2026, the average OEE value was 44,96%, far below the world-class standard of 85%. The component contributing the most was the performance rate (average 64,20%). An analysis of the Six Big Losses identified setup and adjustment losses (12,50%) and equipment failure losses (11,93%) as the largest losses. Through FMEA, the most critical failure modes were hydraulic seal leaks (RPN 432), hydraulic pump failure (RPN 300), and die wear (RPN 280). Improvement proposals based on the TPM pillars were implemented in April 2026 and continued in May 2026, resulting in and increase in the OEE value from 44,96% to 61,92%, demonstrating the continued impact of sustained TPM implementation.